The Challenges of Replicating the Methodology Between Phases I and Iii of the Isaac Programme - Mallol-Villablanca, E (2012)
BACKGROUND: The International Study of Asthma and Allergies in Childhood (ISAAC) used standardised methods to examine symptom prevalence of asthma, rhinitis and eczema in adolescents and children between Phases I and III. Centres followed essential rules to ensure comparability of methodology, examined by a centralised data centre. METHODS: Centre reports (CRs) were compared for both phases and age groups. Methodological differences were categorised under major deviations (centres excluded), minor deviations (deviations identified in published tables) and very minor deviations (deviations not identified). RESULTS: There were 112 CRs for adolescents and 70 for children. Six centres for adolescents and four for children had major deviations and were excluded. Minor deviations (35 for adolescents and 20 for children) were identified in the publications. Very minor deviations (92 for adolescents and 51 for children) were not identified. The odds ratios for having any differences in methodology between phases with a change in Principal Investigator were 0.80 (95%CI 0.36-1.81) for adolescents and 0.91 (95%CI 0.32-2.62) for children. CONCLUSION: The majority of the centres replicated the ISAAC methodology to a high standard. Careful documentation of methodology using standardised tools with careful checks allows the full potential of studies such as ISAAC to be realised. © 2012 The Union.